2020
DOI: 10.1371/journal.pone.0230508
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of intimate partner violence among urban women in sub-Saharan Africa

Abstract: Discussion and conclusion By 2030, the majority of SSA women will be urban dwellers. Complexities surround IPV in urban SSA, highlighting the unique dynamics of the problem in this setting. While affirming the link between IPV and marital power inequities and dynamics, findings suggest that the specific correlates of prevalence rates for different IPV sub-types in urban SSA women can, at once, be both similar and unique. The contextual drivers of the differences and similarities in the correlates of the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 56 publications
13
52
2
Order By: Relevance
“…Five important socio-demographic covariates (level of education, place of residence, wealth quintile, media exposure, and justification of violence) were included in the analysis to adjust for the modelling. The selection of these variables was based on their availability in the datasets and their statistically significant associations with IPV in previous studies ( Ahinkorah et al, 2018 ; Izugbara et al, 2020 ; McCloskey et al, 2016 ; Muluneh, Stulz, Francis, & Agho, 2020 ). In the DHS, level of education was coded as no education, primary, secondary and higher.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five important socio-demographic covariates (level of education, place of residence, wealth quintile, media exposure, and justification of violence) were included in the analysis to adjust for the modelling. The selection of these variables was based on their availability in the datasets and their statistically significant associations with IPV in previous studies ( Ahinkorah et al, 2018 ; Izugbara et al, 2020 ; McCloskey et al, 2016 ; Muluneh, Stulz, Francis, & Agho, 2020 ). In the DHS, level of education was coded as no education, primary, secondary and higher.…”
Section: Methodsmentioning
confidence: 99%
“…In SSA, where IPV has been found to be predominant, several scholars have made efforts to understand the predictors of IPV, with some identifying socio-demographic factors such as age at first marriage, spousal age difference, education, wealth index, place of residence, among other factors as predictors ( Ahinkorah et al, 2018 ; Akamike, Uneke, Uro-Chukwu, Okedo-Alex, & Chukwu, 2019 ; Dim, 2020 ; Izugbara, Obiyan, Degfie, & Bhatti, 2020 ; McCloskey, Boonzaier, Steinbrenner, & Hunter, 2016 ; Yaya, Hudani, Buh, & Bishwajit, 2019 ). Other studies have established an association between women's autonomy or household decision-making capacity and IPV ( Ahinkorah et al, 2018 ; Tenkorang, 2018 ; Zegenhagen, Ranganathan, & Buller, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, collecting data from 22 countries of the Arab league, reveals prevalence ranging from 6% to 59% for physical abuse, from 3% to 40% for sexual abuse and from 5% to 91% for emotional/psychological intimate-partner violence (Elghossain, 2019). Another recent publication highlights similar results in 27 sub-Saharan Africa countries (Izugbara, 2020). In high income countries the rate of GBV is up to 23.2% (WHO, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…There are several reasons why the care needs of this group often remain unnoticed and unaddressed. First of all, survivors of GBV are often unaware that services are available, or they do not seek these services fearing shame and blame (Inter-Agency Standing Commitee, 2015;Oliveira, 2018;Hémono, 2018;Izugbara, 2020). Furthermore, they lack the necessary language pro ciency to access healthcare (Ackerman Rau, 2014;Gehri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sub-Saharan African (SSA) countries standout, with the highest levels of violence against women in the world. 15 It has been reported that 14 out of the 15 countries with the highest level of women who deem wife-beating as justifiable are found in SSA. 16 In SSA countries, many women experience violence in diverse forms, including physical, emotional, psychological and sexual.…”
Section: Introductionmentioning
confidence: 99%